Meningkatkan Kemampuan Komunikasi Matematis Siswa Kelas V SD Negeri 064997 Kecamatan Medan Labuhan Melalui Pendekatan Matematika Realistik - Kirana, Ika Okta (STIKOM Tunas Bangsa Pematangsiantar, 2017)
This study aims to: (1) Improve students 'mathematical communication skills, and (2) Know the effectiveness of applying realistic mathematics learning to students' mathematics learning. This study is a classroom action research conducted in class V SD Negeri 064997 with the number of students as much as 19 people. Instruments used to collect data consist of tests, student and teacher activity observation sheets, and student response questionnaires. The result of the research shows: (1) realistic mathematics learning can improve students' mathematical communication ability, for class classification increased from 68,71% in cycle I to 72,96% in cycle II and 80,99% in cycle III, (2) realistic mathematics learning to the effective learning process mathematics, marked by the achievement of (i) classical mastery of 88.89% above the set criteria that is 85%, (ii) completeness of learning objectives in the third cycle reached 88.88% of students who achieve complete learning objectives 75% for each individual, (iii) the percentage of good category student activity is 77,78% at first meeting and second meeting 83,33% in cycle III, for teacher ability to manage learning equal to 82,05% %, (iv) time efficient, where the application of learning has been carried out in accordance with the time in RPP (v) student response to realistic mathematics learning dika very good categorization, to score the student's response questionnaire of 81.25% in cycle III.